Unity and Contradictions Between Law and Morality in British and Ukrainian Proceedings - Bychkov, Ihor; Ponomarenko, Yuriy A.; Epel, Oksana V.; Belkin, Mark; Kiriushyn, Dmytro (Indonesian Journal of Legal Community Engagement, 2025)
Law and morality are closely interconnected in the regulation of social relations, shaping both legal awareness and social behaviour. In different legal systems, this relationship is manifested through legislation, case law and ethical standards that influence legal decision-making. This study examines how moral principles interact with legal norms in UK and Ukrainian litigation, using a comprehensive methodological approach that includes dialectical, comparative, historical and formal legal analysis. The study highlights how moral and legal dilemmas in judicial decisions affect public trust and perceptions of justice, particularly in cases involving corruption, political influence and human rights. By identifying these problems, the study suggests legal interventions, such as the introduction of amicus curiae mechanisms, strengthening judicial ethics and moral reasoning in judicial decisions, which can better align judicial processes with the values and expectations of the community. This article contributes to the field of legal community engagement by suggesting practical strategies for bridging the gap between formal legal systems and the lived experience of communities. It is particularly relevant to practitioners, policy makers and judicial educators who seek to promote socially responsible justice systems that empower marginalised groups and foster public trust in the rule of law.